Scanning electron microscope analysis of sealant penetration and adaptation in contaminated fissures - Asma Al-Jobair (Wolters Kluwer Medknow Publications, 2013)
Objective: The objective of this study is to evaluate the penetration and adaptation of two different sealant materials applied under different conditions of contamination using scanning electron microscope (SEM) analysis. Materials and Methods: A total of 56 extracted human third molar teeth were randomly assigned into eight equal groups. The treatment groups were defined by the combination of two sealant materials (glass ionomer fissure sealant "Fuji Triage" or resin-based fissure sealant "Clinpro TM") and four surface conditions (dry condition, water contamination, saliva contamination or saliva contamination and air-drying). Penetration depth, sealant adaptation and fissure types were evaluated under SEM after sectioning the teeth. Tukey's test and multiple linear regression analyses were used for statistical analysis. Results: No significant difference in the sealant penetration and adaptation was found between both materials under dry conditions. However, under wet contaminations, resin-based sealant showed less adaptation and penetration with a significant difference when compared to glass ionomer sealant (P < 0.05). The multiple linear regression analyses revealed significant impact of different materials and types of contamination on the sealant penetration and adaptation. Conclusion: Glass ionomer sealant has better fissure penetration and more intimate adaptation than resin-based sealant under wet contamination conditions.